A new compact CPW-Fed dual-band monopole antenna for RFID applications - Ahmed Elhamraoui; El Hassan Abdelmounim; Jamal Zbitou; Ahmed Errkik; Hamid Bennis; Mohamed Latrach (Institute of Advanced Engineering and Science, 2017)
This paper presents a study of a new dual-band monopole antenna fed by a Coplanar Waveguide (CPW) line suitable for Radio Frequency Identification (RFID) applications especially designed for RFID readers and covering free ISM bands of 2.45GHz and 5.8GHz. The proposed antenna benefits from the advantages of the CPW line to simplify the structure of the antenna into a single metallic level, by consequent making it easier for integration with microwave integrated circuits. The simulation of the antenna was carried out using ADS from Agilent technologies and CST Microwave Studio electromagnetic solvers. A good impedance bandwidth of 500MHz is achieved in measurement (from 2.1GHz to 2.6GHz for the lower band), while the upper band covers 800MHz (from 5.2GHz to 6GHz). Details of the proposed antenna design and both simulated and experimental results are described and discussed.